Analysis Of Code Mixing In The Song ‘Come Over (I’m In Tresno)’ By Basboi - Muhammad Fikri; Annisa Karima; Muhammad Rangga Priyatama; Eliana Siagian; Rahmadsyah Rangkuti (Departement of Mathematics Education, 2024)
This research analyzes the use of code-mixing in the song ‘Come Over (I’m in Tresno)’ by Indonesian musician Basboi, emphasizing the innovative application of multilingualism in the lyrics. Code-mixing, the amalgamation of two or more languages inside a single discourse, is a prevalent linguistic occurrence in bilingual populations, and this study investigates its many manifestations in music. The research used a qualitative descriptive technique to identify four kinds of code-mixing in the song's lyrics: insertion (words), insertion (phrases), alternation (clauses), and congruent lexicalization. The results indicate that Basboi adeptly amalgamates English, Indonesian, Javanese, and other languages, illustrating the sociolinguistic complexities of contemporary communication. The recurrent use of code-mixing in his lyrics appeals to multilingual listeners and enhances the cultural and emotional richness of the song. This study underscores the potential of code-mixing as a linguistic and creative instrument, advocating for more research on its prevalence across various musical genres. Furthermore, the results may enhance discourse in sociolinguistics and media studies, especially within bilingual or multilingual frameworks.